2014
DOI: 10.1007/s00464-014-3637-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of recurrence after surgical treatment for liver hydatid cyst

Abstract: Laparoscopic approach for the treatment of liver hydatid cysts was associated with a higher rate of extrahepatic and peritoneal recurrence than open.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 19 publications
1
13
0
1
Order By: Relevance
“…approaches, were originally considered to be the first choice for HCE [20,21]. However, the high probability of postoperative complications and recurrences remains a major problem affecting quality of life an incurring further economic burden [22].…”
Section: Discussionmentioning
confidence: 99%
“…approaches, were originally considered to be the first choice for HCE [20,21]. However, the high probability of postoperative complications and recurrences remains a major problem affecting quality of life an incurring further economic burden [22].…”
Section: Discussionmentioning
confidence: 99%
“…Atli [7] and Unalp [13] reported respectively a cyst diameter above 10.5 and 10 cm as predictive factors of occult intrabiliary cyst rupture with no relation between biliary leakage and nature of the cysts, whether primary or recurrent, single or multiple and their location (right lobe, left lobe or both). This complication could affect the surgeon's choice regarding the surgical approach (Laparoscopy or laparotomy) [30] and the surgical procedure (conservative or radical treatment) [31] . Since cyst-biliary communication is a life-threatening condition, early diagnosis and treatment are mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, a broad-spectrum antibiotic should be chosen for prophylaxis and patients should be treated surgically as early as possible. In addition, suggesting intrabiliary rupture of the liver hydatid cyst can be useful in patient's selection to percutaneous treatment or laparoscopy [30,32,33] . Intraoperative cholangiography should be done systematically [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Radical surgical procedures, such as lobectomy or hepatectomy, have recently been increasingly used in the treatment of hepatic HC, and it has been reported that these procedures have low recurrence, morbidity and mortality rates 31,32 . For example, in the meta-analysis conducted by Buttenscho et al the rates of mortality were reported to be 1.2%, morbidity 11.7% and recurrence 2% 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Jerraya et al reported rates of cure to be 90%, mortality 0.7% and recurrence 6% with conservative approaches for HC 32 . In our The majority of HC cases are asymptomatic, but when symptoms do appear, they include upper right quadrant pain, nausea, vomiting, jaundice and fever 18 .…”
Section: Discussionmentioning
confidence: 99%